2018
DOI: 10.1158/0008-5472.can-17-3014
|View full text |Cite
|
Sign up to set email alerts
|

miR-590-3p Promotes Ovarian Cancer Growth and Metastasis via a Novel FOXA2–Versican Pathway

Abstract: miRNAs play important roles in gene regulation, and their dysregulation is associated with many diseases, including epithelial ovarian cancer (EOC). In this study, we determined the expression and function of miR-590-3p in EOC. miR-590-3p levels were higher in high-grade carcinoma when compared with low-grade or tumors with low malignant potential. Interestingly, plasma levels of miR-590-3p were significantly higher in patients with EOC than in subjects with benign gynecologic disorders. Transient transfection… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
75
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(83 citation statements)
references
References 47 publications
(57 reference statements)
5
75
0
Order By: Relevance
“…As a target gene, FOXA2 has been regulated by various miRNAs, such as miR-1291 and miR-590. 27,28 Consistent with our results, downregulation of FOXA2 has been reported to serve as a tumor suppressor in lung cancer, breast cancer and pancreatic cancer. 18,29,30 In addition, miR-141-3p has been reported to foster cell growth, invasion, and tumorigenesis of cervical cancer by targeting FOXA2.…”
Section: Discussionsupporting
confidence: 90%
“…As a target gene, FOXA2 has been regulated by various miRNAs, such as miR-1291 and miR-590. 27,28 Consistent with our results, downregulation of FOXA2 has been reported to serve as a tumor suppressor in lung cancer, breast cancer and pancreatic cancer. 18,29,30 In addition, miR-141-3p has been reported to foster cell growth, invasion, and tumorigenesis of cervical cancer by targeting FOXA2.…”
Section: Discussionsupporting
confidence: 90%
“…42 Nevertheless, the other study showed that overexpression of miR-320 could promote the invasion and metastasis of ovarian cancer. 45 Zhang et al 14 found that miR-590-3p was downregulated in GEM-resistant T24 cells, unexpectedly, upregulated in our qRT-PCR. For miR-590-3p, it could inhibit cell proliferation, cell migration, and clonogenic activity of head and neck cancer cells.…”
Section: Discussionmentioning
confidence: 57%
“…Moreover, FOXA2 is capable of facilitating EMT, inhibiting apoptosis and enhancing colon cancer cell invasion ability. In OV, miR-590-3p can promote growth and metastasis via the FOXA2-Versican pathway (44).…”
Section: Discussionmentioning
confidence: 99%